Anthropology and the Classics : Six Lectures Delivered Before the University of Oxford - Marett, R. R. (Robert Ranulph), 1866-1943; Evans, Arthur, Sir, 1851-1941; Fowler, W. Warde (William Warde), 1847-1921; Jevons, F. B. (Frank Byron), 1858-1936; Lang, Andrew, 1844-1912; Murray, Gilbert, 1866-1957; Myres, John Linton, Sir, 1869-1954 (Salt Lake City, UT : Project Gutenberg, 2016)
"Anthropology and the Classics" by Arthur J. Evans, Andrew Lang, Gilbert Murray, F.B. Jevons, J.L. Myres, and Warde Fowler is a collection of scholarly lectures delivered at the University of Oxford in the early 20th century. The work delves into the intersection of anthropology and classical studies, focusing on how anthropological insights can illuminate the understanding of ancient Greek and Roman cultures. The book aims to encourage classical scholars to engage with the anthropological perspective, highlighting the significance of lower cultures for a comprehensive view of social evolution. The opening of the text presents a detailed preface that outlines the authors' intentions and the overarching themes of the lectures. It discusses the relationship between anthropology and the humanities, arguing for cooperative exploration of cultural dimensions from both fields. It introduces key figures in the lectures and emphasizes the need to bridge the knowledge of simpler cultures with the complex legacies of ancient Athens and Rome. By laying this foundation, the opening sets the stage for subsequent analyses of topics, such as the evolution of writing systems and ancient rituals, which will be explored in the following lectures. (This is an automatically generated summary.)
The European diffusion of primitive pictography and its bearings on the origin of script, by A.J. Evans -- Homer and anthropology, by A. Lang -- The early Greek epic, by G.G.A. Murray -- Graeco-Italian magic, by F.B. Jevons -- Herodotus and anthropology, by J.L. Myres -- Lustratio, by W.W. Fowler.
Release date is 2016-12-01
E-text prepared by deaurider, Paul Marshall, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Classical philology; Anthropology -- History; Picture-writing